2023
DOI: 10.1021/acs.est.3c02842
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Exposure to UV-328 Impairs the Cell Cycle in Zebrafish (Danio rerio) by Inhibiting the p38 MAPK/p53/Gadd45a Signaling Pathway

Abstract: The benzotriazole UV stabilizer UV-328 is well known for its potent antioxidative properties; however, there are concerns about how it may affect signaling nodes and lead to negative consequences. This study identified the key signaling cascades involved in oxidative stress in zebrafish (Danio rerio) larvae and evaluated the cell cycle arrests and associated developmental alternations. Exposure to UV-328 at 0.25, 0.50, 1.00, 2.00, and 4.00 μg/L downregulated gene expression associated with oxidative stress (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Synthetic phenolic antioxidants (SPAs), amino antioxidants (AOAs), and ultraviolet absorbents (UVAs) are commonly used antioxidants (AOs) in commercial or industrial products, including plastics, , personal care products, rubber, lubricants, and food. , The removal of free radicals by active hydrogen atoms in reactive hydroxyl or amidogen groups prevents the oxidative degradation of products from UV light prolonging their lifespan, as well as oxidation trigged by reactive oxygen species. , The occurrence of specific AOs has been observed previously in various environmental matrices and biota samples, , as a result of long application history, large production volumes, and most importantly nonchemical bonding to materials. These chemicals have sparked increasing public concern in regard to their suspected toxicities, such as carcinogenicity and reproductive and developmental toxicities. …”
Section: Introductionmentioning
confidence: 99%
“…Synthetic phenolic antioxidants (SPAs), amino antioxidants (AOAs), and ultraviolet absorbents (UVAs) are commonly used antioxidants (AOs) in commercial or industrial products, including plastics, , personal care products, rubber, lubricants, and food. , The removal of free radicals by active hydrogen atoms in reactive hydroxyl or amidogen groups prevents the oxidative degradation of products from UV light prolonging their lifespan, as well as oxidation trigged by reactive oxygen species. , The occurrence of specific AOs has been observed previously in various environmental matrices and biota samples, , as a result of long application history, large production volumes, and most importantly nonchemical bonding to materials. These chemicals have sparked increasing public concern in regard to their suspected toxicities, such as carcinogenicity and reproductive and developmental toxicities. …”
Section: Introductionmentioning
confidence: 99%
“…Benzotriazole ultraviolet stabilizers (BUVSs) have been widely applied as additives in supplies such as personal care products, building materials, and automobile components. , The extensive production and consumption of BUVSs resulted in widespread contamination in various environmental media, e.g., surface water, indoor dust, sewage waste, and sediments. BUVSs, with 2-hydroxyphenyl benzotriazole as the parent structure, are highly hydrophobic with octanol/water partition coefficients (log K ow ) of 4.31–7.67 and, thus, can be easily bioaccumulated in tissues of organisms, as reported in animals and humans. Due to the persistence, bioaccumulation, and toxicity, several BUVSs have been listed as Substances of Very High Concern (SVHC) under European Union legislation. Particularly, 2-(3,5-di- tert -amyl-2-hydroxyphenyl)­benzotriazole (UV-328) has been listed in Annex A of the Stockholm Convention on Persistent Organic Pollutants . Besides, a recent survey on the occurrence of frequently used BUVSs in agricultural soils suggested that the BUVS concentrations were several orders of magnitude higher in film-mulched soils (the mean value of 91.4 μg/kg) than those in unmulched soils (the mean value of 0.08 μg/kg), with the level of UV-328 high up to 5.46 × 10 5 μg/kg.…”
Section: Introductionmentioning
confidence: 99%